2018
DOI: 10.3390/rs10060927
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Vegetation and Land Use Types in Fanjingshan National Nature Reserve Using Google Earth Engine

Abstract: Fanjingshan National Nature Reserve (FNNR) is a biodiversity hotspot in China that is part of a larger, multi-use landscape where farming, grazing, tourism, and other human activities occur. The steep terrain and persistent cloud cover pose challenges to robust vegetation and land use mapping. Our objective is to develop satellite image classification techniques that can reliably map forest cover and land use while minimizing the cloud and terrain issues, and provide the basis for long-term monitoring. Multi-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
74
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(91 citation statements)
references
References 41 publications
1
74
0
5
Order By: Relevance
“…soils and vegetation components from satellite imagery. The authors in [15] used machine learning classification in order to map vegetation and land use types. As seen from the abovementioned literature, a lot of work has been done with machine learning to extract vegetation information.…”
Section: Introductionmentioning
confidence: 99%
“…soils and vegetation components from satellite imagery. The authors in [15] used machine learning classification in order to map vegetation and land use types. As seen from the abovementioned literature, a lot of work has been done with machine learning to extract vegetation information.…”
Section: Introductionmentioning
confidence: 99%
“…For more information about the Google Earth Engine, please refer to [36]. In the context of the big data era, the Google Earth Engine cloud platform has powerful data storage and management capabilities and data processing capabilities, providing a technical means for the wide spatial and temporal scales of remote sensing mapping studies [35,[37][38][39]. For example, Hansen et al [40] studied the state of global forest change, at a spatial resolution of 30 m, from 2000 to 2012, by using Google Earth Engine technology and Landsat images.…”
mentioning
confidence: 99%
“…where the coefficients of the EVI equation are L = 1 (canopy background adjustment factor); C1 = 6 and C2 = 7.5 (aerosol correction factors); and G = 2.5 (gain factor) [23,27,63,90]. NIR represents the near-infrared band (TM band 4 and OLI band 5); RED represents TM band 3 and OLI band 4; BLUE represents TM band 1 and OLI band 2 [85,87].…”
Section: Collection Of Landsat Data and Image Compositementioning
confidence: 99%
“…In recent years, GEE has been widely used for global-scale applications such as characterizing global forest cover change; forest expansion, loss, and gain from 2000 using large collections of Landsat scenes [5]; and crop yield estimation [21,22]. Other studies have also confirmed the ease of integrating various sources of temporal satellite imagery data and automating image classification routines for vegetation and land cover mapping using the GEE [17,[21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation